Integrin αvβ6 mediates epithelial-mesenchymal transition in human bronchial epithelial cells induced by lipopolysaccharides of Pseudomonas aeruginosa via TGF-β1-Smad2/3 signaling pathway - Liu, Weiming; Sun, Tieying; Wang, Yong (Folia microbiologica, 2020)
Lower respiratory tract infection due to Pseudomonas aeruginosa has become increasingly challenging, resulting in a worse morbidity and mortality. Airway remodeling is a common phenomenon in this process, to which epithelial-mesenchymal transition (EMT) may contribute as an important promoter. Previous studies showed that epithelium-specific integrin αvβ6-mediated EMT was involved in pulmonary fibrosis via transforming growth factor-β1 (TGF-β1) signaling, but whether integrin αvβ6 plays a role in the P. aeruginosa-associated airway remodeling remains unknown. BEAS-2B cells were incubated with lipopolysaccharide (LPS) from P. aeruginosa in the presence or the absence of integrin αvβ6-blocking antibodies. Morphologic changes were observed by an inverted microscopy. The EMT markers were detected using Western blotting and immunofluorescence. The activation of TGF-β1-Smad2/3 signaling pathway was assessed. Furthermore, matrix metalloproteinase (MMP)-2 and -9 in the medium were measured using ELISA. P. aeruginosa's LPS decreased the expression of the epithelial marker E-cadherin and promoted the mesenchymal markers, vimentin and α-smooth muscle actin in BEAS-2B cells. The expression of integrin αvβ6 was significantly increased during EMT process. Blocking integrin αvβ6 could attenuate P. aeruginosa's LPS-induced EMT markers' expression via TGF-β1-Smad2/3 signaling pathway. Furthermore, blocking integrin αvβ6 could prevent morphologic changes and oversecretion of MMP-2 and -9. Integrin αvβ6 mediates epithelial-mesenchymal transition in human bronchial epithelial cells induced by lipopolysaccharides of P. aeruginosa via TGF-β1-Smad2/3 signaling pathway and might be a promising therapeutic target for P. aeruginosa-associated airway remodeling.
Keywords: pseudomonádové infekce; Lipopolysaccharides; epitelové buňky; Integrins; Epithelial-Mesenchymal Transition; lipopolysacharidy; Epithelial Cells; integriny; Pseudomonas Infections; antigeny nádorové; signální transdukce; Matrix Metalloproteinases; transformující růstový faktor beta1; Smad3 Protein; Signal Transduction; protein Smad2; Transforming Growth Factor beta1; protein Smad3; lidé; Pseudomonas aeruginosa; Humans; matrixové metaloproteinasy; Antigens, Neoplasm; epitelo-mezenchymální tranzice; Smad2 Protein